PENGARUH SELF-EFFICACY TERHADAP KEMAMPUAN PUBLIC SPEAKING MELALUI SELF-CONFIDENCE PADA MAHASISWA MAGISTER FISIP UNIVERSITAS RIAU - Azra, Ahmad Junaidi; Rumyeni; Yazid, Tantri Puspita (Universitas Riau, 2025)
Public speaking ability is an essential skill for master's students to support both academic and professional communication. However, many students still experience difficulties in speaking in public due to low levels of self-efficacy and self-confidence. This study aims to analyze the effect of self-efficacy on public speaking ability with self-confidence as a mediating variable among master's students of the Faculty of Social and Political Sciences, Universitas Riau. The study involved 153 respondents, and the data were collected using questionnaires distributed directly and via Google Forms. Data analysis was conducted using the PLS-SEM method with SmartPLS version 4 software. The results indicate that self-efficacy has a positive and significant effect on public speaking ability, both directly and indirectly through self-confidence. In addition, self-confidence also has a significant influence on public speaking ability. Therefore, enhancing self-efficacy can strengthen self-confidence and positively impact students’ public speaking performance. Keywords: Public Speaking Ability, Self-Confidence, Self-Efficacy